A study of secondary bonding effects in Werner clathrates - Suckling, Adrian Philip (Department of Chemistry, 2016)
The crystal structures of Ni(NCS)₂(4-ViPy)₂.nG where nG = 2CH₂Cl₂ (I), 2CCl₄ (II), 1.8CH₂I₂ (III) and CHI₃ (IV), as well as the crystal structure of [Ni(NCS)₂(4-ViPy)₄]. [Ni(NCS)₂(4-ViPy)₃(thf)].2CHI₃ (V) have been elucidated. The diiodomethane guest molecules in STRUCTURE III were severely disordered at room temperature and so this structure was solved at -40°C. The dichloromethane clathrate is isomorphous with the chloroform clathrate of the same host, and both these clathrates have a similar packing to the carbon tetrachloride clathrate. There is significant secondary bonding between the sulphur (donor) of the isothiocyanate ligand of the host and the iodines (acceptor) of the halogenated guest molecules in compounds III, IV and V. The iodoform clathrates, compounds IV and V, also show strong similarities in their packings. Particular attention has been paid to the shape and size of the cavities in which the guest molecules find themselves, in order to gain a better understanding of the nature of these clathrates. This has also shed some light on the probable cause of the disordered diiodomethane molecules in STRUCTURE III. Packing densities and volume comparisons of the [Ni(NCS)₂(4-ViPy)₂] clathrates have been carried out. Solid - state U.V/visible spectroscopy was used to obtain information on the host conformation, and thermal analysis (thermogravimatry and differential thermal analysis) was used to obtain insight into the host - guest interactions of these clathrates.